Perception of facial esthetics and cephalometric correlations in Class II patients: a comparison between two-phase and one-phase treatments - Wener Chen; Chaoning Zhan; Sze Man Chung; Yifan Lin (Scientific Reports)
Abstract An effective orthodontic treatment should not only aim for satisfactory occlusal outcomes but also consider its impact on facial esthetics. The study aims to evaluate and compare the perception of profile esthetics of skeletal Class II patients treated with two orthodontic modalities: (1) Two-phase approach involving functional appliances followed by fixed appliances with premolar extractions, or (2) One-phase approach using fixed appliances with premolar extractions. Additionally, the study aims to evaluate the correlation between the perceived esthetics and the corresponding cephalometric measurements. The study included 40 skeletal Class II adolescents who underwent either two-phase (n = 20, mean age = 12.38 ± 1.18) or one-phase (n = 20, mean age = 12.53 ± 0.79) orthodontic treatments. Eighty profile silhouettes (pre- and post-treatment) were assessed by 64 raters, including 23 orthodontists, 21 general dental practitioners, and 20 laypersons. The raters used a visual analog scale (VAS) to access profiles, upper and lower lips, and chin esthetics. At pre-treatment, all three groups of raters gave significantly lower scores to the profile silhouettes of the two-phase group compared to the one-phase group (P < 0.01); however, after treatment, they rated the two-phase group significantly higher (P ≤ 0.001). The two-phase group exhibited greater improvements in profile and upper and lower lip esthetics as perceived by all raters (P ≤ 0.001). Furthermore, cephalometric results revealed greater reductions in SNA, ANB, Wits appraisal, and G’-Sn-Pog’ in the two-phase group compared to the one-phase group (P < 0.05). Five cephalometric parameters (SNB, SNPog, overjet, overbite, and UL-SnPog’) demonstrated significant correlations with VAS scores given by orthodontists (P < 0.05). In conclusion, the two-phase group showed greater subjective and objective improvements in facial esthetics than the one-phase group. Additionally, the anteroposterior mandibular position and upper lip protrusion may be the primary cephalometric parameters correlated with subjective facial profile perceptions.